Use of antimicrobial dressings in England and the association with published clinical guidance: interrupted time series analysis - Jo C Dumville; Nicky Cullum; Paul Wilson; Louise Hussey; Susan J Stocks (BMJ Open)
Objectives In healthcare systems, practices and products of unproven value and cost-effectiveness can decrease value and increase waste. Using the management of complex wounds, this study investigates temporal trends in the use of antimicrobials dressings, places this in the context of available evidence and discusses the potential impacts on the UK National Health Service (NHS).Design Secondary descriptive and interrupted time series (ITS) analysis of NHS prescription data.Setting Prescribing Cost Analysis (PCA) details all NHS prescriptions dispensed in the community in England.Interventions An ITS design was used to compare annual changes in the expenditure and use of antimicrobial and non-antimicrobial dressings before and after the publication of the ‘intervention’ of key evidence-based Scottish Intercollegiate Guidelines Network (SIGN) guidance in 2010.Primary and secondary outcome measures Trends in use and expenditure of antimicrobial dressings in relation to published clinical guidance.Results There was a large increase in the prescribing of, and expenditure on, antimicrobial wound dressings between 1997 and 2016. In 1997, the total number of dressings prescribed was 5 792 700; increasing to 11 447 102 in 2009 with expenditure increasing from £1 960 386 to £32 841 263. During the year of the SIGN intervention (2010), there was a significant drop in the use of silver but there was no consistent ongoing reduction from 2011 to 2015.Conclusions Prescribing data can be used to identify products of unproven benefit, which also impose a significant financial burden. This study quantifies the huge increase in the use of antimicrobial wound dressings over a 20-year period despite the lack of compelling evidence to support their routine use. There is some suggestion, however that the use and expenditure decreased after the publication of key guidance. Routine data can be used to as part of more systematic efforts to increase value and reduce waste in health systems.